The effectiveness of brain-breaks exercise intervention on socioecological risks using a transtheoretical model among overweight and obese children in shangrao, China - Liying, Yao (2023)
Childhood obesity has become a significant public health concern globally with multiple contributing factors. To gain a more comprehensive understanding of this issue, this study utilised a combination of the Social-ecological Model and the Transtheoretical Model (TTM) to analyze the social-ecological risk factors among overweight and obese children in China. The Brain-breaks exercise video, specifically designed for classroom settings, was introduced as an intervention tool to enhance children’s physical activity. This study aimed to examine the inter-relationship between TTM variables, social-ecological factors, and physical activity (PA) in different body mass index (BMI) groups and the effect of Brain-breaks exercise videos on the study variables among obese and overweight children in Shangrao City, Jiangxi Province, China. This study was conducted in two phases: a cross-sectional study for Phase 1 and a randomised controlled trial for Phase 2. Cluster random sampling was used to select participants for Phase 1, resulting in the recruitment of 1573 children and adolescents between the ages of 9 and 15. From this group, 100 participants were selected to participate in Phase 2. In Phase 1, eligible participants received a questionnaire package to complete in class, and structural equation modeling was used to examine relationships between study variables. Phase 2 evaluated the effectiveness of Brainbreaks exercise videos, with participants randomised into intervention and control groups for four weeks. Only the intervention group received a daily 10-minute video exercise. Data analysis was performed by SPSS 27.0 and Mplus 8, and the mixed factorial analysis of variance (ANOVA) was used to examine the intervention effects on both groups. In phase 1, most participants were boys (56.8%) with a mean age of 12 years old (SD = 1.68). The final structural model fits the data well [comparative fit index (CFI) = .920, Tucker Lewis index (TLI) = .916, Standardised Root Mean Square Residual (SRMR) = .049, Root Mean Square Error of Approximation (RMSEA) (90% CI) = .039 (.038, .040)]. It also generates significant inter-relationships between TTM variables, social-ecological factors, and the amount of PA. Participants in Phase 2 had a mean age of 13.4 (SD = 2.53) and a mean BMI of 22.8 (SD = 2.22). The intervention group had significantly higher mean scores than the control group on three psychological constructs, including perceived benefits, self-efficacy, and stage of change (p = .006, = .001, < .001, respectively), while the control group had higher scores on perceived barriers (p < .001). The intervention group also had significantly more PA (p = .003). The study concludes that social support is critical for behaviour change in overweight and obese children, and Brain-breaks exercise videos have practical benefits for Chinese overweight and obese children, altering behaviour and motivation towards increased PA.